Solusi Yang Berkeadilan Dari Praktik Gadai Sawah di Perdesaan Pulau Lombok - Moh. Huzaini (Jurnal Ilmiah Ekonomi Islam, 2022)
The aim of this study was to analyze the practice of pawning paddy fields and fair solution in rural areas of Lombok Island. The type of study is descriptive study using qualitative approach since it examines reality, phenomena or symtoms that are holistic, complex, dynamic and meaningful. The data collection techniques were carried out by participatory observation, indepth interviews and decumentation. The informants of this study were farmers who practiced pawning selected in the field through ”purposive” and ”snowball” techniques. The data analysis includes data reduction, data display and drawing conclusions. From this study it can be concluded that the practice of pawning of rice fields committed by the community was due to financial limitation to meet the dharuriyat needs and to obtain business capital. The practice of pawning fields is in accordance with the pillars and condition of pawning based on Islam roles, however it is still inappropriate viewed from the use of collateral since it causes injustice between the pawnbroker (al-rahin) and the pawn receiver (al-murtahin) and indicated elements of usury (ribawi). A fair solution to the practices of pawning paddy fields can commit bai’ al-murabahah contract, mukhabarah/muzara’ah contract, mudharabah contract and Qordul Hasan contract. Of these four contract (aqad), the rice field certipicate is still held by the pawn receiver as a collateral for the debt.